Kitchen concentrations of fine particulate matter and particle number concentration in households using biomass cookstoves in rural Honduras. (March 2020) - Benka-Coker, Megan L.; Peel, Jennifer L.; Volckens, John; Good, Nicholas; Bilsback, Kelsey R.; L'Orange, Christian; Quinn, Casey; Young, Bonnie N.; Rajkumar, Sarah; Wilson, Ander; Tryner, Jessica; Africano, Sebastian; et al.
Abstract: Cooking and heating with solid fuels results in high levels of household air pollutants, including particulate matter (PM); however, limited data exist for size fractions smaller than PM2.5 (diameter less than 2.5 μm). We collected 24-h time-resolved measurements of PM2.5 (n = 27) and particle number concentrations (PNC, average diameter 10–700 nm) (n = 44; 24 with paired PM2.5 and PNC) in homes with wood-burning traditional and Justa (i.e., with an engineered combustion chamber and chimney) cookstoves in rural Honduras. The median 24-h PM2.5 concentration (n = 27) was 79 μg/m 3 (interquartile range [IQR]: 44–174 μg/m 3 ); traditional (n = 15): 130 μg/m 3 (IQR: 48–250 μg/m 3 ); Justa (n = 12): 66 μg/m 3 (IQR: 44–97 μg/m 3 ). The median 24-h PNC (n = 44) was 8.5 × 10 4 particles (pt)/cm 3 (IQR: 3.8 × 10 4 –1.8 × 10 5 pt/cm 3 ); traditional (n = 27): 1.3 × 10 5 pt/cm 3 (IQR: 3.3 × 10 4 –2.0 × 10 5 pt/cm 3 ); Justa (n = 17): 6.3 × 10 4 pt/cm 3 (IQR: 4.0 × 10 4 –1.2 × 10 5 pt/cm 3 ). The 24-h average PM2.5 and particle number concentrations were correlated for the full sample of cookstoves (n = 24, Spearman ρ: 0.83); correlations between PM2.5 and PNC were higher in traditional stove kitchens (n = 12, ρ: 0.93) than in Justa stove kitchens (n = 12, ρ: 0.67). The 24-h average concentrations of PM2.5 and PNC were also correlated with the maximum average concentrations during shorter-term averaging windows of one-, five-, 15-, and 60-min, respectively (Spearman ρ: PM2.5 [0.65, 0.85, 0.82, 0.71], PNC [0.74, 0.86, 0.88, 0.86]). Given the moderate correlations observed between 24-h PM2.5 and PNC and between 24-h and the shorter-term averaging windows within size fractions, investigators may need to consider cost-effectiveness and information gained by measuring both size fractions for the study objective. Further evaluations of other stove and fuel combinations are needed. Graphical abstract: Image 10044 Highlights: Burning solid fuels for cooking produces high concentrations of particulate matter. PM2.5 and particle number concentration (PNC) were moderately correlated. Shorter-term averaging windows were moderately correlated with the 24-h average. Peak concentrations accounted for a substantial portion of 24-h concentration. Abstract : Main Findings: Kitchen concentrations of fine particulate matter (PM2.5 ) and particle number concentration were moderately correlated between traditional and improved biomass cookstoves.